WORDS AND PHRASES OF WHATSAPP IN BAHASA INDONESIA VERSION: TRANSLATION TECHNIQUES AND QUALITY - Nahoras Bona Simarmata (Universitas Pamulang, 2021)
This research tries to find out the translation techniques applied to translate words and phrases in WhatsApp application and how the techniques affect the quality of the translation in terms of accuracy and acceptability. As a descriptive-qualitative research, this research applies purposive sampling. The data are all words and phrases found in the research location, which is WhatsApp application, both in its source language (English) and target language (Bahasa Indonesia). There are 164 data found translated using single variant (137), couplet (26), and triplet (1). They are translated using 9 translation techniques: literal (102), borrowing (60), transposition (10), established equivalent (7), modulation (3), calque (3), linguistic compression (1), and linguistic amplification (2), and reduction (2). They were applied 190 times and resulted in 155 accurate, 5 less accurate, and 4 inaccurate; 149 acceptable, 9 less acceptable, and 6 unacceptable. Calque, linguistic compression, established equivalent, generalization techniques result in accurate and acceptable translations. Meanwhile literal, borrowing, modulation, reduction, transposition techniques result in both lower accuracy and acceptability.